Penggunaan Earned Value Analysis Di Dalam Mengukur Kinerja IT Project - Yuliana Lisanti (Bina Nusantara University, 2010)
IT Project’s succesfulness can be measured from some factors such as project’s time completion, project’s cost and project’s quality. These 3 factors, at least should be as planned, means that on time, on budget and on quality, or better than it has agreed. That’s why a regular project progress update has become a very important factor because it can be used by management to control the project, as well as an alert mechanism or early warning sign whether or not the project is on track or off track. This paper adopts the earned value analysis (EVA) that is used to monitor IT project progress, because EVA is a simple formula whilst able to provide a comprehensive information to support decision making.